Review of Access Policy in the Credit Tranches, the Extended Fund Facility and the Poverty Reduction and Growth Facility, and Exceptional Access Policy. (Policy Papers; Policy Paper ;, 2005)
Section I of this paper contains a discussion of the purpose of access rules, and Section II examines the Fund's liquidity position. Section III discusses the potential demand for Fund resources resulting from several possible shocks. Section IV considers recent trends in access decisions and evaluates how they have conformed to the principles underlying the access rules, and whether the Fund's liquidity would be a constraint to providing similar access in the period ahead. Section V summarizes recent developments in exceptional access and discusses issues pertinent to policy in such cases. Section VI concludes with the list of staff recommendations and the issues for discussion. Draft decisions on access to GRA and PRGF resources are provided in Section VII.